Comparison of platelet count and mean platelet volume values before and after treatment in rheumatoid arthritis and ankylosing spondylitis patients receiving tumor necrosis factor alpha inhibitor therapy - Konur, Sevki; Demirtunc, Refik (Annals of Medical Research, 2021)
Aim: In our study, we planned to reveal the change of the mean platelet volume (MPV) with anti-TNF treatment given in patients with Rheumatoid-Arthritis (RA) and Ankylosing-Spondylitis (AS) and to evaluate the clinical importance of MPV in the follow-up of these diseases.Materials and Methods: Patients who applied to our hospital's between 2011 and 2013 were included in the study. 40 patients participated in the study. The average ages of the patients were 43.8±9.9 years (range:25-68 years). All patients were examined retrospectively, Hemoglobin (Hb), Hematocrit (Hct), Platelet count, Mean Red-Blood-Cell Volume (MCV), MPV, Erythrocyte-Sedimentation-Rate (ESR), C-Reactive Protein (CRP) before anti-TNF treatment were recorded. Then, the same values were checked six months after the treatment. Averages of the Hb, Hct, MCV, PLT, MPV, CRP, ESH parameters of patients before and after treatment were compared with each other.Results: When the values before and after the treatment were compared, there was a significant decrease in ESR (p:0.002). There was also a statistically significant increase in Hb and Hct values after treatment (p:0.002, p:0.039, respectively). A significant decrease was observed in mean platelet count and MPV values after treatment (p:0.001). Although there was an increase in the MCV value, it was not statistically significant. Likewise, there was a decrease in CRP value but it was not statistically significant.Conclusion: In this study, it was concluded that the MPV value and platelet count could be inexpensive biomarkers in the follow-up of RA and AS. However, more controlled prospective studies are needed in this regard.
Keywords: Mean Platelet Volume; anti-TNF; rheumatoid arthritis; ankylosing spondylitis